Carbohydrate digestion and release of pancreatic polypeptide in health and diabetes mellitus. Issue 9 (September 1989) - Layer, P; Go, V L; DiMagno, E P
Abstract : The effects of meal volume and luminal digestion of carbohydrates on the release of pancreatic polypeptide (HPP) were investigated in eight healthy subjects and in six patients who had non-insulin dependent diabetes mellitus. On one occasion each subject ingested a placebo with 200 ml water and a starch (50 g) pudding meal (400 ml) 30 minutes later. On another occasion an amylase inhibitor that retards intraluminal starch digestion was given with the water and starch. In normal subjects, water caused a moderate rise in HPP plasma levels (16.9 (10.9) pg/ml; p less than 0.02) and ingestion of starch increased HPP in a double peaked pattern. The mean increments of the peaks were 45.0 (15.2) pg/ml (p less than 0.02) and 41.1 (17.3) pg/ml (p less than 0.05), respectively. In the diabetic subjects, the HPP concentrations did not increase in response to water. After ingestion of starch the diabetics had two peaks of HPP that were similar in magnitude, but the early postprandial peak was delayed significantly compared to normal subjects (37.5 (5.1) min v 23.4 (3.9) min; p less than 0.05). The amylase inhibitor (5 or 10 g) reduced the early postprandial HPP peak by 79% (p less than 0.05) in normal subjects and 4 g of the inhibitor reduced the early HPP peak by 58% (p less than 0.05) in the diabetics. In both groups ingestion of the amylase inhibitor abolished the late HPP peak (p less than 0.05). In conclusion, carbohydrate induced HPP release is dependent on undisturbed intraluminal starch digestion.